Do organic, conventional, and intensive approaches in livestock farming have an impact on the circulation of infectious agents and antimicrobial resistance? A systematic review, focused on dairy cattle - Pajoro, Massimo; Brilli, Matteo; Pezzali, Giulia; Vadalà, Miriam; Kramer, Laura; Moroni, Paolo; Bandi, Claudio (Frontiers in Sustainable Food Systems, 2024)
Introduction A common thought is that extensive and organic breeding systems are associated with lower prevalence of infections in livestock animals, compared to intensive ones. In addition, organic systems limit the use of anti-microbial drugs, which may lead to lower emergence of antimicrobial resistances (AMR). Methods To examine these issues, avoiding any a priori bias, we carried out a systematic literature search on dairy cattle breeding. Search was targeted to publications that compared different types of livestock farming (intensive, extensive, conventional, organic) in terms of the circulation of infectious diseases and AMR. Results and discussion A total of 101 papers were finally selected. These papers did not show any trend in the circulation of the infections in the four types of breeding systems. However, AMR was more prevalent on conventional dairy farms compared to organic ones. The prevalence of specific pathogens and types of resistances were frequently associated with specific risk factors that were not strictly related to the type of farming system. In conclusion, we did not find any evidence suggesting that extensive and organic dairy farming bears any advantage over the intensive and conventional ones, in terms of the circulation of infectious agents.